2014
DOI: 10.1186/1743-0003-11-13
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating myoelectric-control with transcranial direct current stimulation: a preliminary study in healthy humans

Abstract: BackgroundFunctional Electrical Stimulation (FES) can electrically activate paretic muscles to assist movement for post-stroke neurorehabilitation. Here, sensory-motor integration may be facilitated by triggering FES with residual electromyographic (EMG) activity. However, muscle activity following stroke often suffers from delays in initiation and termination which may be alleviated with an adjuvant treatment at the central nervous system (CNS) level with transcranial direct current stimulation (tDCS) thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…In DDM, the height of the decision threshold reflects response caution where the axonal membrane of ePN may implement a physical threshold [18]. Moreover, the DDM model, and variants of it, are capable of explaining complete response times distributions [13] where our prior work found that anodal tDCS decreased the delay in initiation of muscle contraction and increased delay in termination of muscle activity [2]. In fact, Jo and coworkers [6] alluded to the possibility that negative shifts of the SCPs are related to less effort in starting a movement as compared to positive shifts.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In DDM, the height of the decision threshold reflects response caution where the axonal membrane of ePN may implement a physical threshold [18]. Moreover, the DDM model, and variants of it, are capable of explaining complete response times distributions [13] where our prior work found that anodal tDCS decreased the delay in initiation of muscle contraction and increased delay in termination of muscle activity [2]. In fact, Jo and coworkers [6] alluded to the possibility that negative shifts of the SCPs are related to less effort in starting a movement as compared to positive shifts.…”
Section: Discussionmentioning
confidence: 96%
“…epoch ter ) of dorsiflexion. Here, 500ms duration for epoch ter was selected based on our prior work which showed that even quick termination of muscle activity can take from 492 ms to 514 ms (95% confidence interval) [2]. The first 200ms of each epoch was used for baseline correction, and then the EEG from electrodes Cz, F3, F4, P3, P4 (international 10-20 system) was averaged to compute EEG av .…”
Section: B Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the NIBS to the cerebellum modulates cerebellar excitability [98,[129][130][131], motor function [132,133], and motor learning [32,[134][135][136][137][138] in healthy population. In patients with cerebellar ataxia, some previous studies reported about the effect of tDCS to the cerebellum on motor function [131,[139][140][141].…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%